TINJAUAN TENTANG KUALITAS MAKANAN CAIR SELAMA PENYIMPANAN DI INSTALASI GIZI RSUP DR. M. DJAMIL PADANG - Novianti; Yulia Mandasari (Jurnal Pariwisata Bunda, 2023)
The background of this research was that some patients consumed liquid food after the waiting time and some others didn’t consume liquid food immediately after being received by the patient's family. The results were that the liquid food had changed in taste and color. Liquid food also showed a change in taste after 3 hours of the infusion process. Even though there was no change in the taste of liquid food in the first hour and the second hour of  the cooking process,  there was a change in temperature. The purpose of this study was to look at the quality of liquid food during storage at the nutrition installation at RSUP Dr. M. Djamil Padang. The research method used was the experimental method. Data collection techniques used were documentation studies, questionnaires and literature studies. This study was assessed by a panel of experts on liquid food. The results of this study indicate that the quality of liquid food at 1 hour of storage is very milky, yellowish in color, quite thick in texture and has a very milky and sweet taste. After 2 hours of storage, it has a very milky smell, yellowish in color, quite thick in texture, and has a very milky and sweet taste. Storage for 3 hours, liquid food quality with a milky smell, yellowish color, quite thick texture, milky taste and sweet. Storage for 4 hours, liquid food quality with a milky smell, yellowish color, thick texture, milky taste and sweet taste.